A Convenient Approach to Stereoisomeric Iminocyclitols: Generation of Potent Brain‐Permeable OGA Inhibitors. Issue 51 (6th November 2015) - Bergeron‐Brlek, Milan; Goodwin‐Tindall, Jake; Cekic, Nevena; Roth, Christian; Zandberg, Wesley F.; Shan, Xiaoyang; Varghese, Vimal; Chan, Sherry; Davies, Gideon J.; Vocadlo, David J.; Britton, Robert
Abstract: Pyrrolidine‐based iminocyclitols are a promising class of glycosidase inhibitors. Reported herein is a convenient epimerization strategy that provides direct access to a range of stereoisomeric iminocyclitol inhibitors of O‐GlcNAcase (OGA), the enzyme responsible for catalyzing removal of O‐GlcNAc from nucleocytoplasmic proteins. Structural details regarding the binding of these inhibitors to a bacterial homologue of OGA reveal the basis for potency. These compounds are orally available and permeate into rodent brain to increase O‐GlcNAc, and should prove useful tools for studying the role of OGA in health and disease. Abstract : On the brain : An epimerization strategy provides direct access to a range of stereoisomeric iminocyclitol inhibitors of O‐GlcNAcase (OGA), the enzyme responsible for catalyzing removal of O‐GlcNAc from nucleocytoplasmic proteins. Binding of these inhibitors to a bacterial homologue of OGA was obtained, and it was shown that they permeate in rodent brains.